Assignment: Everything I’ve Learned in Life, I’ve Learned from Society - Jackson, Shirley (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This is an "application" exercise that provides you with the opportunity to show your understanding of basic course concepts by applying them to your understanding of social problems. Using the course material we have read and discussed so far as well as your own personal knowledge, explain how socialization plays an important part in the development of and often, the perpetuation of social problems. Give at least three different examples of social problems. You do NOT need to draw on the course material for your examples – they should be drawn from your own awareness of society on a national, regional, or local basis or perhaps specific to areas like gender, race, age, disabilities, etc.